2013
DOI: 10.1186/cc12786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tyrosine kinase inhibitors, imatinib and nilotinib, in murine lipopolysaccharide-induced acute lung injury during neutropenia recovery

Abstract: IntroductionNeutrophil recovery has been implicated in deterioration of oxygenation and exacerbation of preexisting acute lung injury (ALI). The aim of this study was to investigate whether imatinib or nilotinib was effective on lipopolysaccharide (LPS)-induced ALI during neutropenia recovery in mice.MethodsMice were rendered neutropenic with cyclophosphamide prior to the intratracheal instillation of LPS. Imatinib or nilotinib was administrated by oral gavage during neutropenia recovery. In order to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…For example, imatinib potently suppressed TNF-␣ production and NF-B signaling in macrophages/monocytes stimulated with LPS (61). At the whole animal level, imatinib inhibited the production of cytokines such as IL-6 and attenuated the development of pulmonary edema in a neutropenic model of LPS-induced lung injury and in bleomycin-induced ALI (32,51). The anti-inflammatory effects of imatinib also were evident in a murine model of asthma (5) and in a Bcr-Abl-transfected hematopoietic cell line (4).…”
Section: Discussionmentioning
confidence: 80%
“…For example, imatinib potently suppressed TNF-␣ production and NF-B signaling in macrophages/monocytes stimulated with LPS (61). At the whole animal level, imatinib inhibited the production of cytokines such as IL-6 and attenuated the development of pulmonary edema in a neutropenic model of LPS-induced lung injury and in bleomycin-induced ALI (32,51). The anti-inflammatory effects of imatinib also were evident in a murine model of asthma (5) and in a Bcr-Abl-transfected hematopoietic cell line (4).…”
Section: Discussionmentioning
confidence: 80%
“…Post-treatment with the selective Src-tyrosine kinase inhibitor 4-amino-5-(4-methylphenyl)-7-(t-butyl)pyrazolo [3,4-d]-pyrimidine (PP1) after intratracheal instillation of LPS led to reductions in total protein content in BALF, neutrophil recruitment, nuclear factor (NF)-κB activation, and levels of TNF-α [29]. Treatment with imatinib or nilotinib in LPS-instilled mice during recovery from neutropenia attenuated pulmonary edema, histological changes, and concentrations of TNF-α, IL-1β, IL-6, and myeloperoxidase in BALF [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although advances in supportive care and ventilator management for human ARDS have reduced short-term mortality [2], effective pharmacological therapies are still lacking. In this context, recent studies evaluated the role of tyrosine kinase inhibitors in experimental ARDS [3][4][5]. As major therapeutic agents in oncology, these pharmacological agents block the action of different classes of protein tyrosine kinases (PTKs), important molecules that regulate many intracellular signaling pathways, including the acute inflammatory response to different stimuli [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Abl family kinases, c-Abl (Abl1) and A bl r elated g ene (Arg, Abl2), have recently emerged as key mediators of vascular permeability due to their well characterized roles in the dynamic regulation of the actin cytoskeleton and cell-cell and cell-matrix junctions 58 . Several groups have recently reported that the FDA approved Abl kinase inhibitor imatinib attenuates vascular leak induced by thrombin, histamine, vascular endothelial growth factor (VEGF), lipopolysaccharide (LPS), and oxidative stress 913 . Although the mechanisms are not fully characterized, it is clear that Abl kinase inhibition has potent and pleiotropic effects on vascular barrier function.…”
Section: Inflammatory Vascular Leak: Overviewmentioning
confidence: 99%